KESAKSIAN DUA PEREMPUAN DALAM AL-QURAN: STUDI KOMPARATIF KITAB TAFSIR - A. Latif, Hamdiah (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2018)
Among the interpretation problems of the Al-Qur’an which has broadly attracted the attention of the interpreters of the Al-Qur'an are related to the meaning of justice for the testimony of two women and one male in the Koran. Many exegesis books written (from the classical to the modern period) gave their own understanding and views which strengthened the superiority of men over women because of their weak memories, easy to forget and so on. Some of our other interpretations are of the view that this problem is something that is taken for granted without being able to be questioned, and what is more demanding is submission because it is considered as a part of the issue of worship (ta’abbudiy). This article examines various understandings of the commentaries (classical and modern) which discuss the understanding of the testimony of two women as found in the Qur'an. These problems are increasingly important, especially regarding the interpretation of the Al-Qur’an's view on the issue of gender equality which is increasingly discussed in the current contemporary times.